EVERGREEN PLANTS USED IN THE LANDSCAPING OF CITIES OF UZBEKISTAN (in the example of the city of Tashkent) (International journal of artificial intelligence, 2026)
This article describes the evergreen plants used in the landscape of cities of Uzbekistan, a country with arid and continental climate, and their importance. At the same time, information is provided about the composition of evergreen plants and their importance in urban planning.